2016
DOI: 10.1080/09540121.2016.1178704
|View full text |Cite
|
Sign up to set email alerts
|

Drug use among HIV+ adults aged 50 and older: findings from the GOLD II study

Abstract: Understanding the nexus of aging, HIV, and substance use is key to providing appropriate services and support for their aging, HIV seropositive patients. The proportion of PLWHA aged 50 and older is growing due to a variety of factors like decreases in mortality due to highly active retroviral therapy and non-negligible HIV incidence. We describe prevalence of alcohol, tobacco, and other drug use and participation in substance use treatment and 12-steps programs among 95 HIV-positive patients aged 50 and older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…The potential benefit of medical cannabis in the treatment of patients with HIV has a long history (Werner, 2001) and up to 62% of people with HIV infection report cannabis use (Mimiaga et al, 2013; Okafor et al, 2017; Ompad et al, 2016). Cannabis use could improve HIV outcomes by improving pain and anxiety (both are associated with poor HIV outcomes) or could worsen HIV outcomes, as suggested by pre-clinical studies which show that cannabis negatively impacts immune function (Friedman, Klein, Newton, & Daaka, 1995; Hollister, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The potential benefit of medical cannabis in the treatment of patients with HIV has a long history (Werner, 2001) and up to 62% of people with HIV infection report cannabis use (Mimiaga et al, 2013; Okafor et al, 2017; Ompad et al, 2016). Cannabis use could improve HIV outcomes by improving pain and anxiety (both are associated with poor HIV outcomes) or could worsen HIV outcomes, as suggested by pre-clinical studies which show that cannabis negatively impacts immune function (Friedman, Klein, Newton, & Daaka, 1995; Hollister, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This study is of particular importance as few studies have estimated drug usage among HIV-infected populations in comparison to the general population. The majority of epidemiologic studies report on HIV infection rates among injection drug users in comparison to non-injection drug users [11, 12] or on the prevalence of drug use among a population with HIV [13, 14]. …”
Section: Discussionmentioning
confidence: 99%
“…Existing studies on HIV and drug use in the United States primarily report on HIV infection rates among injection drug users in comparison to non-injection drug users [11, 12] or on the prevalence of drug use among a population with HIV [13, 14]. Few studies, however, have specifically compared drug use patterns among people living with HIV to people without HIV in the general United States population.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike substance use patterns observed among the general population, previous research has suggested that substance use among PLHIV does not decline with age [9]. In one study from the United States (US), 10.5% of OALHIV were found to have used cocaine, 10.5% used crack cocaine, 6.3% used methamphetamines, 7.4% used heroin and 7.4% used prescription opioids without a prescription in the past 12 months [10]. Furthermore, close to a quarter of OALHIV were found to meet the DSM-IV criteria for a substance use disorder [10].…”
Section: Introductionmentioning
confidence: 99%
“…In one study from the United States (US), 10.5% of OALHIV were found to have used cocaine, 10.5% used crack cocaine, 6.3% used methamphetamines, 7.4% used heroin and 7.4% used prescription opioids without a prescription in the past 12 months [10]. Furthermore, close to a quarter of OALHIV were found to meet the DSM-IV criteria for a substance use disorder [10]. Understanding drug use patterns of OALHIV is relevant to improving the health and wellbeing of this population, particularly as drug use has been found to be associated with sub-optimal HIV treatment outcomes, including ART adherence [11].…”
Section: Introductionmentioning
confidence: 99%